Toward Universal Access : Addressing the Global Challenge of Financial Inclusion - Stein, Peer; Randhawa, Bikki; Bilandzic, Nina (International Finance Corporation, Washington, DC, 2015)
This report highlights key trends, challenges, and opportunities for advancing financial inclusion and presents major high-level policy recommendations for consideration by the Group of 20 (G-20) policy makers to benefit a wider range of developing countries, including many non-G-20 countries. The report serves a broad audience, ranging from policy makers, development finance institutions, and the private sector to experts seeking a synopsis of the key subtopics relevant for financial inclusion and areas of work for advancing progress. The report is organized into four sections. The first recommends broad goals and agenda items to accelerate progress in financial inclusion. The second defines the financial inclusion concept and its importance for economic growth and poverty reduction. The third section provides a snapshot of each of the pillars presented as part of the recommendations, and the fourth section summarizes the way forward. The report also contains an annex that takes a closer look at the microfinance industry as a case in point for reviewing the successes, innovations, and lessons learned, which are critical for the broader discussion on financial inclusion.